Tailored Multi-Target Agents. Applications and Design Considerations - Talevi, Alan (Current Pharmaceutical Design, 2016)
Background: In contrast to the one target-one drug paradigm, multi-target agents seem as a promising alternative to manage complex disorders and health conditions linked to drug resistance issues. In fact, many longstanding drugs are in fact unintended multi-functional therapeutics that have emerged from phenotypic screening. The last two decades, however, have witnessed the emergence of tailored multi-target agents, which according to our perspective combine the best aspects of target-based and phenotypic-based drug discovery. Methods: We discuss a number of considerations related to the design, screening and computer-aided discovery of multi-targeted drugs, along with overlooked advantages that this type of agents might have in clinical trials. A theoretic example is included to explain the reduced positive predictive value in virtual screening campaigns focused on multi-target agents. Conclusion: Multi-target agents present great therapeutic potential for the treatment of complex health conditions and the solution of drug resistance phenomena. However, they are certainly challenging for computer-aided drug discovery approaches. Merged or overlapping pharmacophores should be preferred whenever possible. It is thus suggested to perform a careful selection of the combination of pursued targets, preferring target combinations supported by co-evolution or similar biding sites.
Keywords: in silico screening